2019
DOI: 10.1371/journal.pone.0210068
|View full text |Cite
|
Sign up to set email alerts
|

Conophylline inhibits high fat diet-induced non-alcoholic fatty liver disease in mice

Abstract: Conophylline (CnP), a vinca alkaloid extracted from the leaves of the tropical plant Tabernaemontana divaricate, attenuates hepatic fibrosis in mice. We have previously shown that CnP inhibits non-alcoholic steatohepatitis (NASH) using a methionine-choline-deficient (MCD) diet-fed mouse model. However, little is known about the CnP mediated inhibition of hepatic steatosis in high-fat diet-induced non-alcoholic fatty liver disease (NAFLD) mouse models. CnP (0.5 and 1 μg/g/body weight) was co-administered along … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 43 publications
(59 reference statements)
1
16
0
Order By: Relevance
“…PPAR α expression was positively correlated with the expression of CPT-1. Namely, PPAR α regulates the levels of CPT-1, an enzyme essential for β -oxidation of long-chain fatty acids [ 35 , 36 ]. The present study indicated a similar tendency of PPAR α and CPT-1 expressions [ 37 , 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…PPAR α expression was positively correlated with the expression of CPT-1. Namely, PPAR α regulates the levels of CPT-1, an enzyme essential for β -oxidation of long-chain fatty acids [ 35 , 36 ]. The present study indicated a similar tendency of PPAR α and CPT-1 expressions [ 37 , 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…Fat-enriched diets providing 32–45% [ 55 , 56 , 57 , 58 ] or 60% kcal fat [ 59 , 60 , 61 , 62 , 63 ] are a well-established approach to NAFLD in rodents. However, in our model, evaluating the anti-NAFLD effects of curcumin was problematic.…”
Section: Discussionmentioning
confidence: 99%
“…Changing dietary habits and reduced physical activity has increased the incidences of NAFLD to an alarming proportion, and presently, 25% of the world’s population is affected by NAFLD. It is pertinent to note that the onset of NAFLD is considered as the hepatic response of metabolic syndrome and in the absence of any preventive measures, NAFLD can progress towards other irreversible liver complications such as NASH, liver fibrosis, cirrhosis, and hepatocellular carcinoma [ 30 , 31 ]. Liver is one of the principal organs involved in lipid metabolism, and abnormal functioning of cellular pathways involved in lipid deposition and lipid metabolism facilitates the accumulation of lipid in hepatocytes, leading to excessive lipid deposition in the liver [ 32 ].…”
Section: Discussionmentioning
confidence: 99%